Addressing the CO2 emissions of the world's largest coal producer and consumer: Lessons from the Haishiwan Coalfield, China. (1st February 2015) - Li, Wei; Younger, Paul L.; Cheng, Yuanping; Zhang, Baoyong; Zhou, Hongxing; Liu, Qingquan; Dai, Tao; Kong, Shengli; Jin, Kan; Yang, Quanlin
Abstract: China is now the world's largest user of coal, and also has the highest greenhouse gas emissions associated with the mining and use of coal. In the mining sector, the interests of workforce safety coincide with those of GHG (greenhouse gas) management. While the traditional approach to ensuring workforce safety in coal mines was simply to vent the hazardous gases to the atmosphere, thus increasing GHG emissions, recent innovations have seen elements of CCS (carbon capture and storage) being used to simultaneously ensure workforce safety and minimization of GHG emissions. The Haishiwan Coalfield represents a particularly challenging environment for applying this approach, as the coal-bearing strata host both oil shales and a naturally-occurring CO2 reservoir, disturbance of which could both imperil workers and lead to elevated GHG emissions. A low-carbon, CCS-based model of gas management developed in the Haishiwan Coalfield offers attractive lessons for application to other coal mines, within and beyond China. This approach achieves multiple benefits: energy production, enhanced workforce safety and minimization of GHG emissions. Given the extreme nature of the Haishiwan case, it ought to be even easier to implement these approaches elsewhere. Highlights: Boreholes coalbed CO2 capture involving oil shales pyrolysis and retorting gas power generation. A gas hydrate separation and CO2 injection into abandoned mine for CO2 capture and storage. A low-carbon, CCS-based model of gas management developed in the Haishiwan Coalfield.